PENERAPAN PSAP BERBASIS AKRUAL PERNYATAAN NO.5 ATAS AKUNTANSI PERSEDIAAN PADA BALAI BESAR KIMIA DAN KEMASAN - Berliana Deborah Miranda (2023)
The purpose of writing this Final Project Report is to find out the suitability of Inventory Accounting according to PSAP No. 5 at the Center for Chemical and Packaging. Inventory is a current asset in the form of goods acquired with the aim of supporting government operations or a form of service to the community. Inventories are regulated in Government Accounting Standards Statement Number 5 on Inventory Accounting which aims to support the orderly and smooth administration of inventory items. Inventories are recorded on an accrual basis, that is, records are made at the time a transaction occurs either at the time of use or at the time of obtaining the inventory. This accrual basis can improve efficiency and effectiveness in accountability for the use of APBN funds. The Center for Chemical and Packaging implements this PSAP to support transparent and responsible supply administration. Data and information to support this writing were collected by conducting literature searches, relevant source searches, internet searches, and observations at the Center for Chemistry and Packaging. The results of the study show that Inventory Accounting is in accordance with PSAP Number 5, namely inventory is recognized when the potential future economic benefits are obtained by the government and have a value or cost that can be measured reliably, when received or ownership rights and or control transfers.